Peran Lembaga Pendidikan Islam dalam Menentukan Corak Peradaban Masyarakat di Era Globalisasi - Yusuf Yusuf (Proceedings of Annual Conference for Muslim Scholars, 2017)
The flow of globalization greatly affects and challenges the implementation of Islamic education that impact can be felt in today’s society civilization. This research aims to describe and analyze how the role of Islamic educational institution can determine the pattern to a better civilization in the era of globalization. The results of this research is expected to provide more in-depth information about how the Islamic education institutions to respond to the challenges experienced toward existence as education providers. This research is a qualitative descriptive study using a natural background for the purpose of interpreting the phenomena that occurred and was done by involving a variety of method e exist. The results showed that Islamic educational institutions play a role in determine pattern to better society civilization in terms of maintaining and improving the quality of education providers.Keywords: Islamic educational institution, civilization cociety, era of globalization